KAJIAN POTENSI RIZOBAKTERI PEMACU PERTUMBUHAN TANAMAN YANG DIISOLASI DARI RIZOSFER PADI SEHAT - AYU KADE SUTARIATI, GUSTI; RAKIAN, TRESJIA CORINA; -, AGUSTINA; SOPACUA, NOVITA; -, LA MUDI; HAQ, MUBAYYINUL (Jurnal Agroteknos, 2014)
The experiment was carried out to characterize the ability of rhizobacteria isolated from the rhizosphere of healthy lowland rice in dissolving phosphate or fixing nitrogen.  The research was conducted from February to June 2011 at Agronomy Laboratory, Agriculture Faculty, Halu Oleo University. The experiment was arranged based on descriptive methods. Overall, the number of isolates characterized were 40 isolates.  The results of the isolate characterization were documentated with specific indicators (eg. the ability to dissolve phosphate in the form of halo/clear zone). The research indicated that most of these isolates had the ability to dissolve phosphate and fix nitrogen.  Isolates PKNW 6, PKMN 7,  PKNS 3, PKNS 9 and PKNW 4 showed better ability in dissolving phosphate and fixing nitrogen than other isolates evaluated. Further studies are still needed for the development of the potential isolates as biological agensts or biofertilizer. Keywords: healthy rice rhizosphere, rhizobacteria, fix nitrogen, dissolve phosphate